2021
DOI: 10.1111/aen.12559
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcode identification of Conopomorpha cramerella (Snellen, 1904) (Lepidoptera: Gracillariidae) and other moths affecting cacao in Papua New Guinea

Abstract: Economically important cacao (Theobroma cacao Linnaeus 1753) plantations in South East Asia and Papua New Guinea (PNG) are significantly affected by the cocoa pod borer (CPB) moth. Species identity of the pest is attributed to Conopomorpha cramerella (Snellen 1904), a gracillariid moth endemic to Australasian and Oriental tropic regions that has evolved a host preference for introduced cacao. Suspected presence of cryptic CPB biotypes is largely unsupported by earlier genetic work but remains a concern to orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(77 reference statements)
2
2
0
Order By: Relevance
“…The other CPB haplotypes were found in low frequencies, in cocoa and rambutan and diverged by up to 0.3%. This low intraspecific genetic diversity has also been reported in previous studies that sampled widely (Gopurenko et al, 2021; Reynolds et al, 2019; Shapiro et al, 2008). The CPB low genetic diversity characterized to date allows the development of additional more rapid diagnostic tests such as the ones mentioned above.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The other CPB haplotypes were found in low frequencies, in cocoa and rambutan and diverged by up to 0.3%. This low intraspecific genetic diversity has also been reported in previous studies that sampled widely (Gopurenko et al, 2021; Reynolds et al, 2019; Shapiro et al, 2008). The CPB low genetic diversity characterized to date allows the development of additional more rapid diagnostic tests such as the ones mentioned above.…”
Section: Discussionsupporting
confidence: 82%
“…The molecular approach used here revealed the presence of an undetermined Conopomorpha sp. caught in pheromone traps in the forests surrounding Tavilo (this study), which was identical to a larva from cocoa also from ENB (Gopurenko et al, 2021;Reynolds et al, 2019). More Conopomorpha species are expected to be discovered given the recent biodiversity studies that have identified Gracillarid moths as a hugely diverse group (Brito et al, 2016;Kawahara et al, 2017;Lees et al, 2014;Lopez-Vaamonde et al, 2018Sam et al, 2017)…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Examples of molecular markers used for insect population studies are: mitochondrial DNA cytochrome oxidase I (mtDNA COI), coding nuclear elongation factor-1α (EF-1α) marker, randomly amplified polymorphic DNA (RAPD), restriction site associated DNA (RAD) and microsatellites [ 12 , 13 ]. Microsatellite markers are short tandem DNA repeats of one to six nucleotides and are widely used for population genetic analysis, as they are abundant in most genomes, are highly polymorphic, Mendelian, co-dominant, and can be easily amplified by polymerase chain reaction (PCR) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%